Electoral systems, poverty and income inequality - Darwin Urgarte Ontiveros; Vincenzo Verardi (Luxembourg Income Study (LIS), 2005)
In this article we use the high-quality data coming from the Luxembourg Income Study Project, in a panel framework, to test for the effects of electoral systems on both poverty and income inequality. We find that when de degree of proportionality of an electoral system increases, inequality and poverty decrease. We also find than in presidential regimes, the levels of poverty and inequality are higher than in parliamentary regimes.
Keywords: 330; Wahlverhalten; Einkommensverteilung; Disparitätsmaß; Gini-Koeffizient; Öffentliche Sozialleistungen; Europa